Association of Engineering and Shipbuilding Draughtsmen - Notes made from wireless bulletins (?) (page 2)
"Association of Engineering and Shipbuilding Draughtsmen - Notes made from wireless bulletins (?) (page 2)" [g0973002.jpg], n.d.